Zooplankton abundance from microscopic analyses of Multinet and WP2 net samples during the MOSAiC expedition (PS122) in the Arctic Ocean - Cornils, Astrid; Niehoff, Barbara; Knüppel, Nadine; Ashjian, Carin; Campbell, Robert G; Castellani, Giulia; Gelfman, Cecilia; Hildebrandt, Nicole; Sakinan, Serdar; Schaafsma, Fokje L; Schmidt, Katrin; Shoemaker, Katyanne; et al. (In: Cornils, A et al. (2025): Zooplankton abundance and biovolume from Multinet and WP2 net samples during the MOSAiC expedition (PS122) in the Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980504, 2025)
Depth-stratified mesozooplankton samples were collected in the Arctic Ocean from 2019 to 2020 multinet midi (Hydrobios, 150 µm mesh, opening 0.25 m2) and with a WP2 net (150 µm, 0.38 m2) during the MOSAiC expediton with PV Polarstern (PS122). In approximately weekly intervals, we conducted vertical tows at mostly five depth intervals 0 – 50 m, 50 – 200 m, 200 – 500 m, 500 – 1000 m and 1000 – 2000 m. The volume of filtered water was recorded with a digital flowmeter. All net samples were preserved in a 4% formaldehyde seawater solution buffered with Borax onboard. The samples were analyzed via microscopy to the lowest taxonomic level possible.
Keywords: Abundance; Arctic; biovolume; MOSAiC20192020; Multinet; Zooplankton; ZooScan